Chalcogenide Microsphere‐Assisted Optical Super‐Resolution Imaging. Issue 6 (9th January 2022) - Xie, Yu; Cai, Dawei; Pan, Jing; Zhou, Ning; Guo, Xin; Wang, Pan; Tong, Limin
Abstract: Microsphere‐assisted optical imaging has been proved straightforward and cost‐effective for super‐resolution imaging in material science and biomedical research. Optically transparent microspheres with a high refractive index are critical for achieving superior super‐resolution capabilities yet remain to be further exploited. Here, the use of As2 S3 (an optically transparent chalcogenide glass) microspheres, with a refractive index as high as 2.31 (at 600 nm) and diameters ranging from 10 to 215 µm, for optical super‐resolution imaging is reported. Under white‐light illumination (peaked at 646 nm), As2 S3 microspheres full‐immersed in polymethyl methacrylate or immersion oil generate super‐resolved virtual images of nanostructures (≈90 nm in minimum feature size) with a magnification up to 8×. The lateral resolution of full‐immersed microspheres, which can be as low as ≈172 nm for a 19 µm diameter As2 S3 microsphere, is also investigated. Moreover, super‐resolved real imaging of nanostructures with semi‐immersed As2 S3 microspheres is demonstrated for the first time. Compared with the full‐immersion approach (e.g., for a 30 µm diameter microsphere, the image plane is ≈30 µm underneath the specimen with a magnification of 4.3×), the semi‐immersion approach provides an obvious improvement in the magnification (6.6×) and a much longer operation distance to the objective (the image plane is ≈140 µm above the specimen). Abstract : Super‐resolution imaging based on optically transparent high‐refractive‐index As2 S3 ( n  ≈ 2.31 at 600 nm) microspheres is demonstrated. Under white‐light illumination, As2 S3 microspheres full‐immersed in a polymethyl methacrylate (PMMA) film or immersion oil generate super‐resolved virtual images of nanostructures (≈90 nm in minimum feature size) with a magnification up to 8×. Semi‐immersing microspheres in a PMMA film for super‐resolved real imaging is also demonstrated.